2001
DOI: 10.2527/2001.7982075x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for lean growth efficiency in Duroc pigs influences pork quality.

Abstract: A unique line of Duroc pigs was established by intensive selection for increased lean growth efficiency. The objective of this study was to determine the influence of this selection strategy on fresh pork quality traits. Two lines of Duroc pigs originating from the same foundation herd were evaluated. One line was selected for lean growth efficiency over five generations (Select line), and the other was a contemporary line maintained from the foundation herd (Control line). All pigs in the trial tested negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
128
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 37 publications
11
128
0
4
Order By: Relevance
“…Traditionally, it has been accepted that DU is a fatter breed than PI (Nieuwhof et al, 1991;Ellis et al, 1996). However, Lonergan et al (2001) found that selection for lean growth efficiency in DU resulted in lines with more lean gain and higher percentage of carcass lean at the expense of fat. -P Saturated fatty acids (SFAs) 5 C10:0 1 C12:0 1 C14:0 1 C15:0 1 C16:0 1 C17:0 1 C18:0 1 C20:0.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, it has been accepted that DU is a fatter breed than PI (Nieuwhof et al, 1991;Ellis et al, 1996). However, Lonergan et al (2001) found that selection for lean growth efficiency in DU resulted in lines with more lean gain and higher percentage of carcass lean at the expense of fat. -P Saturated fatty acids (SFAs) 5 C10:0 1 C12:0 1 C14:0 1 C15:0 1 C16:0 1 C17:0 1 C18:0 1 C20:0.…”
Section: Discussionmentioning
confidence: 99%
“…Autolysis lowers the amount of calcium needed for activation of calpain-1 (Suzuki et al, 1981). Calpain-1 in muscle degrades the proteins desmin, troponin-T, and titin during postmortem aging in beef (Huff-Lonergan et al, 1996a) and pork (Lonergan et al, 2001;Melody et al, 2004). The rate of activation and autolysis of calpain-1 could impact the amount of protein degradation by calpain-1.…”
Section: Discussionmentioning
confidence: 99%
“…Lonergan et al (2001) suggested that the selection for lean growth efficiency in pigs has lead to a decrease in postmortem proteolysis of myofibrillar protein. Xiong et al (2006) reported that, when RAC is fed, porcine muscle tended to have a slower protein degradation rate for proteins in the 15Á45 kDa range.…”
Section: Discussionmentioning
confidence: 99%